PERAN ORANG TUA DALAM MENDORONG MOTIVASI BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Amelia, Maya; Alani, Nabella; Hakim, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students’ motivation to learn, particularly in mathematics in elementary school, is quite low given that students perceive mathematics as a difficult subject, and this can affect their learning outcomes. Students’ motivation to learn is closely linked to one important factor: the support provided by the family environment, particularly parents. This study was conducted with the aim of providing an overview of the influence of parental roles on elementary school students’ motivation to learn mathematics. This study employed a qualitative research design. Data were collected through interviews with three parents and three students. The results indicate that there are differences in students’ levels of learning motivation based on the support provided by their parents. Students who received strong parental support were more active, confident, and enthusiastic in participating in lessons. Conversely, students who received less support tended to exhibit lower learning motivation. These findings demonstrate that parental involvement plays a crucial role in fostering elementary students’ motivation to learn mathematics.